The Relationship Among Demographic Factors, Transition Services, and Individual Development Account (IDA) Saving Participation Among Transition-Age Youth With Disabilities. (October 2021) - Jones, Weneaka D.; Phillips, Brian N.; Hartman, Ellie; Bishop, Malachy; Tansey, Timothy N.; Anderson, Catherine A.
Saving participation in adolescence is crucial for young adults to achieve financial well-being over their lifetime. Yet, very little is known about the factors that encourage saving participation among youth with disability, including youth who receive supplemental security income (SSI). This study examines relationships between personal and family factors, transition services, and participation in Wisconsin Promoting Readiness of Minors in Supplemental Security Income (PROMISE) individual development account (IDA), within a sample of youth with disabilities who receive SSI. Results of the hierarchical binary logistic and hierarchical multiple regression analyses suggests that the PROMISE interventions variable sets emerged as the most frequent predictors of IDA saving participation among youth receiving SSI. Specifically, work incentive benefits consultation services, financial capability-focused financial coaching services, and self-advocacy training were significant predictors of a youth's IDA saving participation. This study's findings offer important implications for transition planning and building financial capability.